Neutrophil‐endothelial interactions of murine cells is not a good predictor of their interactions in human cells. Issue 2 (23rd December 2019) - Soroush, Fariborz; Tang, Yuan; Mustafa, Omar; Sun, Shuang; Yang, Qingliang; Kilpatrick, Laurie E.; Kiani, Mohammad F.
Abstract: All drugs recently developed in rodent models to treat inflammatory disease have failed in clinical trials. We therefore used our novel biomimetic microfluidic assay (bMFA) to determine whether the response of murine cells to inflammatory activation or anti‐inflammatory treatment is predictive of the response in human cells. Under physiologically relevant flow conditions, permeability and transendothelial electrical resistance (TEER) of human or mouse lung microvascular endothelial cells (HLMVEC or MLMVEC), and neutrophil‐endothelial cell interaction was measured. The differential impact of a protein kinase C‐delta TAT peptide inhibitor (PKCδ‐ i ) was also quantified. Permeability of HLMVEC and MLMVEC was similar under control conditions but tumor necrosis factor α (TNF‐α) and PKCδ‐ i had a significantly higher impact on permeability of HLMVEC. TEER across HLMVEC was significantly higher than MLMVEC, but PKCδ‐ i returned TEER to background levels only in human cells. The kinetics of N ‐formylmethionyl‐leucyl‐phenylalanine (fMLP)‐mediated neutrophil migration was significantly different between the two species and PKCδ‐ i was significantly more effective in attenuating human neutrophil migration. However, human and mouse neutrophil adhesion patterns to microvascular endothelium were not significantly different. Surprisingly, while intercellular adhesion molecule 1 (ICAM‐1) was significantly upregulated on activated HLMVEC, it was not significantly upregulated on activated MLMVEC. Responses to activation and anti‐inflammatory treatment in mice may not always be predictive of their response in humans.